Quality assessment of Primary Health Care Centers as perceived by child caregiver in Najaf Governorate - Ahmed A. Ali; Mahmoud S.Thamer; Salam J. Mohammed (Genius Journals, 2023)
The quality of healthcare services provided by Primary Health Care Centers is of utmost importance to ensure that individuals and families receive timely, appropriate, and effective care. The assessment of healthcare quality from the perspective of patients and caregivers is crucial to identify areas for improvement and to develop strategies for enhancing the quality of care provided.
Keywords: Primary health care; quality; Najaf governorate